Pengaruh Kelembapan, Suhu Udara dan Curah Hujan terhadap Kejadian Kebakaran Gambut di Kabupaten Tanjung Jabung Timur, Jambi - Erianto Indra Putra; Idelia Lathiifah Puspadewi (Jurnal Silvikultur Tropika, 2020)
Tanjung Jabung Timur Regency, Jambi has a serious problem with peatlands fires. The effects of humidity, air temperature and rainfall are often associated with climatic influences that provide ideal conditions for fire to occur. The results of the study clearly showed that air humidity, air temperature, and rainfall contributed to the number of hotspot. Humidity was the variable with highest correlation of -0,569. The decrease of humidity that followed by a decrease in rainfall and an increase in air temperature from June to September 2019 led to the highest hotspot in September 2019, which resulted to an increase of forest fire occurrences in Tanjung Jabung Timur, Jambi. Keywords: fire, peatlands, temperature, rainfall, humidity